1996
DOI: 10.1002/(sici)1097-0142(19961215)78:12<2465::aid-cncr3>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Diet and exercise regimens to improve breast carcinoma prognosis

Abstract: Breast carcinoma patients wishing to change their lifestyle are likely to benefit from a higher dietary fiber/fat ratio combined with regular physical exercise. If the trial shows an improved prognosis from intervention correlated with changes in biomarkers, a similar trial model could be used to identify specific fiber supplements, micronutrients, and exercise regimens that may improve survival rates in patients with breast carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 69 publications
0
14
0
Order By: Relevance
“…Another proposed hypothesis is related to insulin resistance [26]. It has been postulated that chronically elevated insulin level is associated with breast cancer [27], and it is known that obesity [28] and physical inactivity [29] are two of the main environmental determinants of insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Another proposed hypothesis is related to insulin resistance [26]. It has been postulated that chronically elevated insulin level is associated with breast cancer [27], and it is known that obesity [28] and physical inactivity [29] are two of the main environmental determinants of insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past two decades, studies on cancer prognosis and lifestyle factors have been conducted, but they were focused mainly on neoplasms of breast (6,(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26), larynx (27), lung (28), and oral cavity (26,29), as well as malignancies in the upper digestive tract (30). Over the past two decades, studies on cancer prognosis and lifestyle factors have been conducted, but they were focused mainly on neoplasms of breast (6,(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26), larynx (27), lung (28), and oral cavity (26,29), as well as malignancies in the upper digestive tract (30).…”
Section: Discussionmentioning
confidence: 99%
“…It is concluded that nutritional and lifestyle modifications that improve insulin sensitivity may not only decrease the tendency to atherosclerosis, but also reduce breast cancer risk in women (33). Insulin resistance may be a marker of increased breast cancer risk, and trials of an increased n‐3:n‐6 PUFA ratio in the diet, together with regular physical exercise, have been proposed against both conditions (4).…”
mentioning
confidence: 99%